Pemberdayaan Masyarakat Pesisir Melalui Diversifikasi Olahan Ubur-Ubur Sebagai Produk Ekonomi Kreatif Berbasis Potensi Lokal - Ari Widiati; Ridwan Ridwan; Danan Muhuda AS; Samsul Hidayat; Zaenuddin Zaenuddin; Nur Atiqah; Eka Junila Saragih; Abdurrahman Abdurrahman; Raziki Waldan (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2026)
Indonesia, as a maritime nation, has a long coastline and vast waters with abundant marine resource potential. This potential includes capture fisheries, aquaculture, and various economically valuable marine biota scattered throughout coastal areas, including Temajuk Village, Sambas Regency, West Kalimantan. However, this vast marine resource potential has not been optimally utilized to improve community welfare. This study aims to analyze community empowerment strategies based on local potential through the development of creative economic products processed from marine products and their implications for improving community welfare. The study used a qualitative method with a case study approach. The data used consisted of primary and secondary data obtained through observation, interviews, and documentation. Data analysis was carried out through the stages of data condensation, data presentation, and conclusion drawing. The results of the study indicate that community empowerment based on local potential can encourage improvements in the welfare of coastal communities. Innovation in processing jellyfish into creative products such as satay and pecel provides added economic value by increasing the selling price of raw materials by up to 70%, reducing dependence on middlemen, increasing the average income of business actors by 40%, and strengthening the culinary identity of Temajuk Village in a sustainable manner.